The Relationship between Entrepreneurship and Unemployment in Japan - André van Stel; Roy Thurik; Ingrid Verheul; Lendert Baljeu (Tinbergen Institute, 2007)
This paper examines the relationship between entrepreneurship (as measured by fluctuations in the business ownership rate) and unemployment in Japan for the period between 1972 and 2002. We find that, although Japan's unemployment rate has been influenced by specific exogenous shocks, the effects of entrepreneurship on unemployment are not different when compared to other OECD countries. In the past, small firms in Japan benefited from the protective environment of the keiretsu structure. This secure environment no longer exists, and a new market environment conducive to new venture creation and growth has not yet been established. We argue that the Japanese government should actively stimulate an entrepreneurial culture.
Keywords: J23; J64; L26; O11; O53; 330; entrepreneurship; business ownership; unemployment; Japan; Entrepreneurship-Ansatz; Selbstständige; Unternehmensgründung; Arbeitslosigkeit; Beschäftigungseffekt; Vergleich; Japan; OECD-Staaten